2021
DOI: 10.3389/fimmu.2021.794642
|View full text |Cite
|
Sign up to set email alerts
|

Reactogenicity and Immunogenicity of the Pfizer and AstraZeneca COVID-19 Vaccines

Abstract: BackgroundThe relationships of the coronavirus disease 2019 (COVID-19) vaccination with reactogenicity and the humoral immune response are important to study. The current study aimed to assess the reactogenicity and immunogenicity of the Pfizer and AstraZeneca COVID-19 vaccines among adults in Madinah, Saudi Arabia.MethodsA cross-sectional study, including 365 randomly selected adult Pfizer or AstraZeneca vaccine recipients who received a homologous prime-boost vaccination between February 1st and June 30th, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…Other studies failed to identify a correlation between adverse events and the IgG titers one month following the BNT162b2 vaccination, but the same authors identified sex and body weight as predictors of the incidence of adverse events [ 20 ]. Our data confirm that female gender and younger age are significantly associated with adverse events, and this may reflect the more efficacious immune response observed in women for SARS [ 21 ] and other vaccines [ 22 ], particularly at a younger age. Among adverse events, lymphadenopathy has been observed in 78.4/100,000 subjects after the SARS-Cov-2 vaccination, more frequently axillary and unilateral [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 80%
“…Other studies failed to identify a correlation between adverse events and the IgG titers one month following the BNT162b2 vaccination, but the same authors identified sex and body weight as predictors of the incidence of adverse events [ 20 ]. Our data confirm that female gender and younger age are significantly associated with adverse events, and this may reflect the more efficacious immune response observed in women for SARS [ 21 ] and other vaccines [ 22 ], particularly at a younger age. Among adverse events, lymphadenopathy has been observed in 78.4/100,000 subjects after the SARS-Cov-2 vaccination, more frequently axillary and unilateral [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 80%
“…Some previous studies had obese individuals among their study population, but these studies did not intensively investigate whether obesity affects COVID‐19 vaccine effectiveness. 24 , 25 , 26 , 27 , 28 Moreover, immunoassays that only determine the presence of anti‐SARS‐CoV‐2 antibodies, but do not assess their neutralizing activity, were utilized in most of these studies. Hence, we aimed to investigate the effectiveness of various S‐based COVID‐19 vaccines in inducing anti‐S IgG antibodies among individuals with various classes of obesity (class I, II, III, and super obesity).…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies indicate that AEs decrease with age, the associations identified between AEs and antibody responses are largely based on studies involving small cohorts and/or differences in analytical strategies (21)(22)(23)(24)(25)(26)(27). Furthermore, studies have not addressed whether T-cell responses correlate with AEs.…”
Section: Specific Cd4 + T-cell Responsementioning
confidence: 99%
“…Notably, AEs have been more frequently observed after the second dose and with higher severity than after the first dose (14), which strongly suggested that AEs are a consequence of immunological memory induced by the adaptive immune system. However, previous reports did not reach a consensus concerning the association between AEs and vaccine-induced immune reactions, such as antibody production, likely due to the small cohorts used in the studies and variations in how AEs were defined (21)(22)(23)(24)(25)(26)(27). Moreover, most studies examined the associations of AEs with antibody levels and/or neutralizing activity but not with T-cell responses, which can result in the production of cytokines and thus cause systemic effects.…”
Section: Main Text: Introductionmentioning
confidence: 99%